Aerobic versus resistance training effects on health-related quality of life, body composition, and function of older adults - Flavia Accioly Canuto Wanderley (2015)
This study aimed to investigate the effects of training on health-related quality of life (HRQoL), body composition, and function in older adults. Fifty participants were randomized into aerobic training (AT-70%-80% HRreserve), resistance training (RT-80% IRM), or controls. They had HRQoL, body composition, and function assessed before and after 8 months. Training groups reduced body fat, increased performance in the stair ascent, 8-ft up-and-go and sit-to-stand five-times tests, and improved their physical component score (PCS; p <= .03). AT increased performance in the 6MWT test, and improved general and mental health (MH) domains when compared to controls (p < .01). Finally, changes in stair ascent were associated with changes in bodily pain, MH, and mental component score (p <= .04), while changes in handgrip strength were associated with changes in physical role and MH (p = .03). AT and RT were effective interventions for decreasing body fat and improving functionality and the PCS in older adults.